Wavefront sensing for objective assessment of vision therapy efficacy: preliminary results - Gomes, Jéssica Rafaela Moreira (2023)
The aim of this study was to use wavefront sensing to objectively evaluate the effects of vision therapy in subjects with insufficiency (AI) and infacility of accommodation (AINF). Aberrometry was performed with a Shack-Hartmann wavefront aberrometer for different accommodative stimuli in one subject with AI and one with AINF before and after treatment with vision therapy (VT). A control subject received a placebo treatment. Real-time accommodative response, accommodation and disaccommodation reaction time, accommodative microfluctuations and root mean square of higher order aberrations were compared before and after VT/placebo. VT was effective and wavefront sensing can be used to detect AI and AINF and evaluate these subjects during VT.